2018
DOI: 10.32598/bcn.9.6.448
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Process in Patients With Obsessive-Compulsive Disorder: A Cross-Sectional Analytic Study

Abstract: Introduction:In recent studies, deficit in cognitive process has been investigated as one of the etiological hypotheses in a wide range of Obsessive-Compulsive Disorder (OCD). This research aimed to compare cognitive process in patients with OCD and healthy groups.Methods:In the current cross-sectional analytic study, 43 patients with OCD and 43 healthy individuals matched with gender, age, educational and marital status were selected by convenience sampling method and assessed by Wisconsin Cart Sorting Test (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 45 publications
0
6
0
1
Order By: Relevance
“…In 2016, Habibi et al reported that the content validity of this questionnaire is both convergent and divergent. Additionally, the reliability of this questionnaire has been calculated with Cronbach’s alpha coefficient 0.90 ( 32 ).…”
Section: Methodsmentioning
confidence: 99%
“…In 2016, Habibi et al reported that the content validity of this questionnaire is both convergent and divergent. Additionally, the reliability of this questionnaire has been calculated with Cronbach’s alpha coefficient 0.90 ( 32 ).…”
Section: Methodsmentioning
confidence: 99%
“…Apabila dikaitkan dengan faktor karakteristik responden, resiliensi yang tercipta dapat didukung dengan lansia yang memiliki usia lebih lama dibandingkan golongan usia lainnya karena lansia memiliki lebih banyak pengalaman hidup yang membantu dalam membentuk kemampuan serta sudut pandang untuk menghadapi berbagai situasi (Yazdi-Ravandi et al, 2013). Status pernikahan dan tinggal bersama pasangannya juga menjadi salah satu faktor yang memungkinkan dalam membantu meningkatkan resiliensi lansia.…”
Section: Pembahasanunclassified
“…Previous research has found that patients with OCD exhibit deficits in cognitive set-shifting, as evidenced by their WCST performance. 9 …”
Section: Introductionmentioning
confidence: 99%